2017
DOI: 10.1186/s13104-017-2416-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the feasibility of eHealth and mHealth: a systematic review and analysis of initiatives implemented in Kenya

Abstract: BackgroundThe growth of Information and Communication Technology in Kenya has facilitated implementation of a large number of eHealth projects in a bid to cost-effectively address health and health system challenges. This systematic review aims to provide a situational analysis of eHealth initiatives being implemented in Kenya, including an assessment of the areas of focus and geographic distribution of the health projects. The search strategy involved peer and non-peer reviewed sources of relevant information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 35 publications
1
73
0
6
Order By: Relevance
“…A unique aspect of this study was the use of the MAPS Toolkit, which allowed for comprehensive evaluation of the major components needed to introduce and adopt the EIRs as part of the scale-up plan. The EIRs deployed in Tanzania and Zambia were planned for scale prior to piloting the systems; this is a rare occurrence in LMICs where limited numbers of DHIs are scaled following a pilot or "proof-of-concept" deployment [6,7,17]. The variability in the success of EIR adoption is seen by the range of use amongst districts across each country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique aspect of this study was the use of the MAPS Toolkit, which allowed for comprehensive evaluation of the major components needed to introduce and adopt the EIRs as part of the scale-up plan. The EIRs deployed in Tanzania and Zambia were planned for scale prior to piloting the systems; this is a rare occurrence in LMICs where limited numbers of DHIs are scaled following a pilot or "proof-of-concept" deployment [6,7,17]. The variability in the success of EIR adoption is seen by the range of use amongst districts across each country.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study help to provide needed context to understand the degree of sustained use, which in turn influences the resulting immunization coverage. Successfully scaling up of a DHI is contingent on the intervention demonstrating an impact on health outcomes, which continues to remain a challenge as there are few studies that assess impact on clinical outcomes in LMICs [6,17,24]. Researchers and policy makers have recognized that an implementation science agenda is needed to help expand the breadth of relevant evidence available for DHIs, this includes conducting more mixed methods and quasi-experimental studies that can help understand the influence of contextual factors on implementation of an intervention [26].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Gorski et al (2016) found from their meta-analysis that globally, most mHealth projects are located in sub-Saharan Africa [ 16 ]. According to Njoroge et al (2017), the growth of mHealth in sub-Saharan Africa is particularly outstanding in Kenya [ 17 ]. However, former studies have not attempted to quantitatively and systematically assess the mHealth and mobile penetrations in sub-Saharan Africa region.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, health system experts emphasize more on the maintenance and evaluation (23) . Currently, more research has been done to know the user acceptance and use of IT across the world as the key component of health IT lifecycle (24,25) . The latest model "Unified Theory of Acceptance and Use of Technology (UTAUT)" proposed by the researchers included all the possible determinants of user acceptance.…”
Section: Discussionmentioning
confidence: 99%